2023
DOI: 10.1093/glycob/cwad004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Streptococcus mutans PgfE and GalE 4-epimerases in protein glycosylation, carbon metabolism, and cell division

Abstract: Streptococcus mutans is a key pathogen associated with dental caries and is often implicated in infective endocarditis. This organism forms robust biofilms on tooth surfaces and can use collagen binding proteins (CBPs) to efficiently colonize collagenous substrates including dentin and heart valves. One of the best characterized CBPs of S. mutans is Cnm which contributes to adhesion and invasion of oral epithelial and heart endothelial cells. These virulence properties were subsequently linked to post-translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In S. pyogenes and S. pneumoniae , we elucidated a novel Glc-type O -linked glycosylation mechanism in which glycosyltransferase GtrB initiates the synthesis of a Glc-modified bactoprenol-phosphate lipid molecule for the transfer of Glc to extracytoplasmic proteins harboring the Ser/Thr-rich IDRs. Previous studies have reported that S. mutans possesses the O -linked protein glycosylation system encoded by the Pgf gene cluster which covalently links N-acetylhexosamine sugars, presumably GalNAc and GlcNAc, with the cell wall-associated adhesins Cnm and WapA 32, 33 . Like GtrB in S. pyogenes and S. pneumoniae , the Pgf-encoded glycosyltransferase, PgfS, initiates the protein glycosylation pathway 27, 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In S. pyogenes and S. pneumoniae , we elucidated a novel Glc-type O -linked glycosylation mechanism in which glycosyltransferase GtrB initiates the synthesis of a Glc-modified bactoprenol-phosphate lipid molecule for the transfer of Glc to extracytoplasmic proteins harboring the Ser/Thr-rich IDRs. Previous studies have reported that S. mutans possesses the O -linked protein glycosylation system encoded by the Pgf gene cluster which covalently links N-acetylhexosamine sugars, presumably GalNAc and GlcNAc, with the cell wall-associated adhesins Cnm and WapA 32, 33 . Like GtrB in S. pyogenes and S. pneumoniae , the Pgf-encoded glycosyltransferase, PgfS, initiates the protein glycosylation pathway 27, 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Pgf pathway glycosylates PrsA, PBP1a, FtsQ and PknB with GalNAc in S. mutans Contrary to S. pyogenes and S. pneumoniae, no ConA-bound proteins were recovered from solubilized extracts of the S. mutans membranes. However, S. mutans possesses a protein glycosylation machinery that decorates the cell wall-associated collagenbinding adhesins WapA and Cnm with O-N-acetylhexosamines, presumably Nacetylgalactosamine (GalNAc) and N-acetylglucosamine (GlcNAc) 32,33 . O-Glycosylation of WapA and Cnm requires the participation of the Pgf gene cluster encoded enzymes: the GtrB-type glycosyltransferase PgfS, an epimerase PgfE, and two GT-C fold glycosyltransferases PgfM1 and PgfM2.…”
Section: Ser/thr-rich Idrs Are Glucosylated In S Pneumoniaementioning
confidence: 99%
“…In summary, G. mellonella has been used for testing many infections caused by different gram-positive and gram-negative bacteria. Among gram-positive microorganisms, Staphylococcus aureus [ 71 , 72 , 73 , 74 , 75 , 76 , 77 ], Streptococcus pyogenes [ 78 , 79 , 80 ], Streptococcus pneumoniae [ 81 , 82 , 83 ], Streptococcus mutans [ 19 , 20 , 84 , 85 , 86 ], L. monocytogenes [ 4 , 44 , 65 , 66 , 87 , 88 ], Enterococus faecalis [ 89 , 90 , 91 , 92 ], Enterococcus faecium [ 93 , 94 , 95 , 96 ], L. rhamnosus GG [ 63 , 64 ], C. butyricum Miyairi 588 [ 63 ], C. perfringens [ 67 , 68 ], Mycobacterium bovis [ 23 ], Mycobacterium abscessus [ 97 , 98 ], and Mycobacterium tuberculosis [ 99 , 100 , 101 , 102 ] were mentioned. Among gram-neg...…”
Section: General Characterization Of G Mellonela A...mentioning
confidence: 99%
“…Our group demonstrated that the Pgf machinery is required for the post-translational glycosylation of both core (WapA) and non-core (Cnm) LPXTG-anchored surface proteins (Avilés-Reyes et al, 2018). In addition to the LPXTG anchoring motif, Cnm possesses an amyloidogenic β-sheet-rich Collagen-Binding Domain (CBD) (Cologna et al, 2021) and a Threonine-Rich Repeat Region (TRRR) where O-glycosylations with HexNAc 2 moieties (presumably GalNAc and GlcNAc) have been identified (Andresen et al, 2023). Deletion of the pgf genes in OMZ175 results in a reduction of both Cnm and WapA molecular weights and stability.…”
mentioning
confidence: 99%
“…Moreover, these deletions significantly hinder Cnmassociated virulence traits such as binding to collagenous surfaces, invasion of endothelial and epithelial cells, and killing of Galleria mellonella, an invertebrate model of systemic infection (Avilés-Reyes, Miller, Simpson-Haidaris, Hagen, et al, 2014;Avilés-Reyes et al, 2018). Furthermore, apart from Cnm and WapA, we have recently identified two other potential targets of Pgf glycosylation: the surface-anchored SpaP (also known as Antigen I/II or P1) and the glucosyltransferase GtfC, which is involved in glucan biosynthesis as part of sucrose-dependent biofilm formation (Andresen et al, 2023).…”
mentioning
confidence: 99%